Entwerfen und Konstruieren mit gekrümmtem Glas. Issue 1 (25th March 2019) - Fildhuth, Thiemo; Oppe, Matthias; Schieber, Roman
Abstract : Design and Construction with Curved Glass . Driven by free‐form design and improved manufacturing methods, curved glass is increasingly used in modern architecture. Permanent curvature is obtained by thermal bending, whereas elastic cold bending results in a reversible curved glass shape stabilized by fixing upon a substructure or by lamination with shear‐stiff interlayers. However, for the application in building projects mutually depending factors such as the geometrical shape and curvature, glass dimensions, residual stress, applicability for IGUs, coatings, the interlayer or the optical quality have to be respected. The present paper contributes to creating a design basis regarding the use of curved architectural glass by comparing typical properties, assets and limitations of the above‐mentioned types and by illustrating their application through project examples.